The Political Parties as Organisations of Representation of the Political Rights of Individuals in Albania - Klajdi Mone (Academicus International Scientific Journal, 2014)

(untitled)
According to the Constitution or laws, individuals today have extensive political rights closely associated with the right to vote. Here is meant the active and passive right of voting. Membership in a party is not only because of the desire, but also for the fact that the party gives individuals the possibility of career progress, further realization of their political rights. The purpose of this paper is to present the development of political parties and individual rights, not only in Albania, but also combined with the European experience. In this paper we will focus on how political parties have evolved as well as the political rights of individuals after the independence in 1912. The development of political parties in Albania has passed in two stages in the communist system where only one party was known and in the democratic system where was recognized political pluralism. Highlighting the role of political parties, as an important promoter of the functioning of state and of the coverage of the political rights of individuals, makes this study important.